Corporate Hierarchies under Employee Representation - Filippo Belloc; Gabriel Burdin; Fabio Landini (Institute of Labor Economics (IZA), 2020)
This paper analyzes whether workplace employee representation (ER) affects the design of firm hierarchies. We rationalize the role of ER within a knowledge-based model of hierarchies, where the firm's choice of hierarchical layers depends on the trade-off between communication and knowledge acquisition costs. Using a sample of more than 20000 private-sector workplaces in 32 countries, we document conditional correlations between ER and the depth of hierarchy that are consistent with our framework. The presence of ER is positively associated with the number of organizational layers, though the relationship is tempered by firm size. Additional instrumental variable estimates reinforce our main result. ER positively correlates with job training and skill development, suggesting that the effect of ER (if any) is to reduce knowledge costs. Moreover, ER is associated with enhanced internal communication via staff meetings. The analysis of managers' perceptions suggests the higher frequency of meetings in firms with ER does not lead to more delays in the implementation of organizational changes. Taken together, our findings suggest that ER increases the depth of firm hierarchy by facilitating the flow of information to top decision makers, possibly through skip-level reporting, and hence reducing communication costs.
Keywords: J51; L23; M11; 330; organization; firm hierarchy; employee representation; European Company Survey